Loan and Inheritance Patterns in Hunter-Gatherer Ethnobiological Systems. Issue Volume 34:Issues 2(2014) (July 2014) - Bowern, Claire; Haynie, Hannah; Sheard, Catherine; Alpher, Barry; Epps, Patience; Hill, Jane; McConvell, Patrick
We compare the etymologies of ethnobiological nomenclature in 130 hunter-gatherer and agriculturist languages in Australia, North America, and Amazonia. Previous work has identified correlations between systems of ethnobiological terminology and dominant means of community subsistence, relating stability of terminology to the "salience" of the items. However, the relevance of subsistence patterns to the development of ethnobiological nomenclature requires further investigation, as does the notion of "salience" and how it might relate to etymological stability. The current study probes the relationship between salience and stability and the variability within this relationship. We refine the notion of stability by studying both inheritance and loan rates. We refine the notion of "salience" by separately testing retention and loan rates in flora and fauna vocabulary that might be considered salient for different reasons. Results indicate that the most etymologically stable items are core foodstuffs (whether cultivated or wild). Psychotropic items were more likely to be loaned. There were no significant patterns for cultivar status or trade, though we note that the most frequently loaned items in the sample are also traded.